Negotiating marriage, family and work : experiences of middle class Egyptian women - Roque, Dahlia Tawhid (Abingdon, Oxon ; New York, NY : Routledge, 2020)
Caught between two worlds of social transition and modern progression, young women in the Middle East have for some time been forging means to balance conventional gender roles and marriage expectations, while also advancing their position in society through improved legal status, health and educational attainment. Yet, with half of Egypt's university-educated women out of the labour market and not seeking work, this study reveals why middle-class women continue to pursue a degree that they fail to use. This book sheds light onto the lives of highly educated middle-class Egyptian women, where they share their stories of spouse selection and marriage, and how education, wealth and unyielding gender roles influence their employment status.Through qualitative ethnography, Negotiating Marriage, Family and Work gives voice to young Egyptian women, both married and single, presenting their self-perceptions, their roles as mothers and wives, and their agency. Carried out from the time of the Arab Spring, this research uncovers the key strategies that middle-class women employ to secure their economic well-being in their marital and domestic contexts, as well as the barriers that married women face in combining paid work and family care.
OCLC-licensed vendor bibliographic record.
Keywords: Middle class women -- Egypt -- Social conditions; Sex role -- Egypt; Women -- Employment -- Egypt; Married women -- Egypt; Work and family -- Egypt; SOCIAL SCIENCE / General; SOCIAL SCIENCE / Sociology / General